SISTEM INFORMASI PEMASARAN USAHA KECIL MENENGAH (UKM) BERBASIS WEBSITE - Indrayani, Lilis; Awopi, Feri; Zabir, Suriani (DINAMIS, 2020)
The marketing information system for small and medium enterprises (SMES) based on the village of Bulukumba district Tritiro is expected to be able to provide a picture of information and transaction sales of products at UKM Konjo roof. The research aims to: (1) Designing a marketing information system for small and medium enterprises (SMES) based websites in the village of Tritiro Bulukumba District, (2) implementing a marketing system of small and medium enterprises (SMES) based websites on the village Tritiro. This method of research is conducted using interview methods, observations and documentation. System design is done with the modeling language using the Unified Modelling Language (UML) consisting of Use case diagrams, activity diagrams and sequence diagrams. While the programming used is HyperText Markup Language (HTML), Cascading Style Sheets (CSS), Hypertext Preprocessor (PHP), JQUERY using a MySQL database. Testing the program using the Blackbox method as the final stage in the creation of this application, with the test results free of logic errors. This results showed that with the information system of marketing of small and Medium enterprises (SMES) based website in the village of Tritiro Bulukumba District can facilitate the crowd see the products contained in certain SMES and can make purchases of products for South Sulawesi region and Admin in processing product purchases from customers and view sales reports. As for the features that appear on the website are the homepage, SME village Tritiro, shopping products, about and login menu for customers and admins